Mobile Operators as Banks or Vice-Versa? and: Regulators’ Interest in the Best Efficiency of Payments - Pau, Louis François (Discoveries in Agriculture and Food Sciences, 2015)
This paper addresses the strategic challenges of deposit banks, and payment clearinghouses, posed by the growing role of mobile operators as collectors and payment agents for flows of cash for themselves and between third parties. Through analysis and data from selected operators, it is shown that mobile operators as money flow handlers achieve levels of efficiency, profitability, and risk control comparable to deposit banks. Furthermore, the payment infrastructures deployed by both are found to be quite similar, and are analyzed in relation to financial profitability, strategic challenges and opportunities This paves the way to either mobile operators taking a bigger role, or for banks to tie up such operators to them even more tightly, or for alliances/mergers to take place, all these options being subject to regulatory evolution which is analyzed as well. The consequences of the payment efficiency and architectures are mapped out in operational and regulatory terms.